Chemical Characterization of Different Extracts of Justicia secunda Vahl and Determination of Their Anti-Oxidant, Anti-Enzymatic, Anti-Viral, and Cytotoxic Properties - Łukasz Świątek; Elwira Sieniawska; Kouadio Ibrahime Sinan; Gokhan Zengin; Anastazja Boguszewska; Benita Hryć; Kouadio Bene; Małgorzata Polz-Dacewicz; Stefano Dall'Acqua (MDPI AG, 2023)
Justicia secunda Vahl. is a traditional medicinal plant in tropical regions, including West Africa. The present study examined the chemical profiles and biological properties of J. secunda extracts obtained with different solvents (dichloromethane, ethyl acetate, methanolic and aqueous: macerated and infused). Chemical components were characterized by liquid chromatography-mass spectrometry (LC-MS), and over 50 compounds were identified, including flavonoids, phenolic acids, and alkaloids. Antioxidant, enzyme inhibitory, cytotoxic, and antiviral properties were selected as biological properties. Total phenolic and flavonoid contents in methanol (58.07 mg gallic acid equivalent (GAE)/g and 13.07 mg rutin equivalent (RE)/g) and water (infused) (36.34 mg GAE/g and 8.52 mg RE/g) were higher than in other extracts. Consistent with the levels of total bioactive components, the methanol and water extracts exhibited stronger antioxidant abilities. However, the dichloromethane and ethyl acetate extracts were more active on α-amylase and α-glucosidase than other extracts. Aqueous extracts exerted selective anticancer properties toward human pharyngeal cancer cell lines, whereas the methanolic extract decreased the human herpesvirus type-1 (HHV-1) infectious titer by 2.16 log and the viral load by 1.21 log. Overall, J. secunda could be considered a multifunctional bioactive raw material in the preparation of potent applications to manage diseases related to oxidative stress, including cancer, diabetes, and Alzheimer's.